The presence of blaIMP genes on plasmids DNA isolated from multidrug-resistant Pseudomonas aeruginosa strains at University Hospital in Bialystok (Poland)--first report. - Piotr Wieczorek; Tomasz Hauschild; Marcin Zórawski; Paweł Sacha; Jadwiga Jaworowska; Piotr Jakoniuk; Elzbieta Tryniszewska (Folia Histochemica et Cytobiologica, 2008)
Resistance to carbapenems is emerging, and it is a great problem to therapeutics. Seven multidrug-resistant (MDR) of Pseudomonas aeruginosa strains were isolated from urine and bronchial specimens. All isolates showed resistance to imipenem and meropenem (MIC; > or =16 mg/L). The resistance to carbapenems in two of seven strains was associated with the production of a metallo-beta-lactamases. Plasmids DNA probes were used to investigate the presence of genes coding for IMP-type enzymes. PCR experiments revealed that bla(IMP) genes were present in two isolates of Pseudomonas aeruginosa (MIC >32 microg/mL for both carbapenems).